Comparative Activities of Doripenem versus Isolates, Mutants, and Transconjugants of Enterobacteriaceae and Acinetobacter spp. with Characterized β-Lactamases - Mushtaq, Shazad (American Society for Microbiology, 2004)
Doripenem (S-4661), a new parenteral carbapenem, was tested against over 250 clinical isolates, mutants, and transconjugants of Enterobacteriaceae and Acinetobacter spp., selected or derived for their β-lactamase expression characteristics. Imipenem, meropenem, and ertapenem were tested as comparators, along with cephalosporins and piperacillin-tazobactam, by using National Committee for Clinical Laboratory Standards agar dilution methodology. Doripenem MICs were from 0.03 to 0.25 μg/ml for Klebsiella isolates, irrespective of the presence of extended-spectrum β-lactamases (ESBLs) or plasmid-mediated AmpC or hyperproduced K1 β-lactamase. Similarly, MICs of doripenem for both AmpC-inducible and -derepressed Enterobacter isolates were 0.06 to 0.5 μg/ml. ESBL production did not raise the MICs of doripenem for Escherichia coli transconjugants, and studies with known expression mutants confirmed that neither inducible nor depressed AmpC β-lactamase expression was protective in Enterobacter cloacae, Citrobacter freundii, Serratia marcescens, or Morganella morganii. In all of these respects, doripenem resembled meropenem and imipenem, whereas the MICs of ertapenem were raised (but still ≤1 μg/ml) for many ESBL-producing klebsiellas and AmpC-derepressed E. cloacae and C. freundii strains. Resistance to all carbapenems, including doripenem (MICs of mostly 16 to 64 μg/ml, compared with 0.25 to 1 μg/ml for typical strains), was seen in Acinetobacter isolates with metallo-β-lactamases or OXA-carbapenemases. Isolates of Klebsiella and Serratia spp. with IMP, KPC, and SME β-lactamases also were resistant to doripenem (MICs, 8 to >64 μg/ml) and to other carbapenems, although the continued apparent susceptibility (MICs, ≤0.5 μg/ml) of E. coli derivatives with cloned IMP-1 and NMC-A β-lactamases suggested that carbapenem resistance might require other factors besides the enzymes.